PERANCANGAN APLIKASI VIDEO CONFERENCE UNTUK BIMBINGAN TUGAS AKHIR - Sampebua, Mingsep; Nugroho, Lukito E.; Istiyanto, Jazi E.; Hidayat, Risanuri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Video conference application to long distance guidance is a real time communication application service used to organizes consultation conference in Internet. The online consultation application can support text communication, face-to-face communication, dialogue-based communication, and sharing se- minar material presentation. The design of the online consultation application program consists of three parts,  which  are  a server  application program,  a lecturer application program and a student application program. The importance of the real time communication in organizing online consultation system is its capability to create virtual environment (Internet) as a replication of real world communication, because it supports text communi- cation, file presentation, face-to-face communication and direct dialogue between participants. The  face-to-face  communication  and  direct  dialogue  can  create  a dynamic interaction environment, because participants can interact face-to-face, directly talk to each other, obtain feedback, present physical reaction of other participants, and chatting using text communication. It become a solution to the problem of distance and time for meeting activities of two or more individuals using internet. The result of the research are sequence diagram and class diagram de- sign. Sequence diagram is used to representation communication scenario. Class diagram  is  used  to  representation  communication  functions.  That  contains group functions and rules/processes necessary in communication. The classes formed in the class diagram design are directly used as object classes at im- plementation level in the form of online consultation application program code